2021
DOI: 10.21003/ea.v187-18
|View full text |Cite
|
Sign up to set email alerts
|

The role of Islamic marketing ethics for customer loyalty in Islamic banking through customer satisfaction

Abstract: This study aims to build a conceptual and empirical model of Islamic marketing ethics’ influence on Islamic banks’ customer loyalty through customer satisfaction on salesperson services and customer satisfaction to Islamic banks over the year 2020. This study develops a new theoretical model, namely the ethical behaviour of Islamic marketing which is predicted to influence customer loyalty in Islamic banks by integrating customer satisfaction variables. The marketing ethics measurement model in the current res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These positive results are associated with existing literature, i.e. Fianto et al (2020), Thaker et al (2020), Nasuka et al (2021) and Suhartanto et al (2022). The results demonstrate that Pakistani microbusiness owners are loyal to their institutions and think they are loyal to them.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These positive results are associated with existing literature, i.e. Fianto et al (2020), Thaker et al (2020), Nasuka et al (2021) and Suhartanto et al (2022). The results demonstrate that Pakistani microbusiness owners are loyal to their institutions and think they are loyal to them.…”
Section: Discussionsupporting
confidence: 85%
“…Different perceptions of consumers and loyalty satisfy the consumers for Islamic and non-Islamic banks (Fianto et al , 2020). Customer loyalty, directly or indirectly through customer satisfaction, may develop through Islamic ethical behaviour (Nasuka et al , 2021). In Indonesia, the factors such as trust and service quality are the dominant elements of millennial loyalty towards mobile banking (Suhartanto et al , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This has not escaped the attention of researchers focused on Islamic banking. For instance, several studies report that satisfaction positively correlates with loyalty intentions for customers at the Islamic bank (Lubis et al, 2021;Nasuka et al, 2021;Tegambwage and Kasoga, 2022). Nonetheless, research is needed to advance the understanding of Islamic banks in different environments, particularly the role that different cultural features play on the relationship between satisfaction and loyalty (Dandis et al, 2021).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The results also show that consumers cannot mediate products, prices, places, promotions, processes, people and physical evidence to consumer loyalty. Nasuka (2021) built a conceptual and empirical model of the effect of Islamic marketing ethics on Islamic bank customer loyalty through customer satisfaction with salesperson services and customer satisfaction at Islamic banks during 2020. The results showed that Islamic ethical behavior has a significant effect on customer loyalty directly or indirectly through customer satisfaction.…”
Section: Cluster 3: Islamic Marketing and Customer Loyaltymentioning
confidence: 99%